Gaslighting as a psychological violence: understanding the phenomenon from the perspective of Behavior Analysis - Moreira, Julia Lue de Freitas Minaré; Oliveira, Paula Grandi de (Perspectivas em Análise do Comportamento, 2023)
Gaslighting, a frequent type of psychological violence in abusive relationships and hardly recognized, occurs when the aggressor uses offenses, humiliation, threats, etc. to communicate to the victim that their perceptions, thoughts and feelings are incorrect or inadequate. This paper aims to broaden the discussion on the phenomenon of gaslighting from a behavioral-analytic perspective, analyzing the main behavioral patterns present in the practice of this violence and what maintains them. An interpretive exercise was made, relating the literature that describes the phenomenon of gaslighting with the behavioral-analytic literature, through the concepts: coercion, tact of private events and rule-governed behavior. These concepts were defined and related to examples of gaslighting victims, taken from journalistic reports and books. The analysis pointed out raised behavioral patterns present in both the aggressor’s and the victim’s behaviors, with behaviors controlled by contingencies of punishment, negative reinforcement and social rules, in addition to the distorcion of the victim’s tacts of private events. As we live in a patriarchal society that shapes male and female behavioral repertoires and contributes to inequality between genders, it is important to study phenomena such as gaslighting and other topics related to violence against women and patriarchy from a behavioral-analytic perspective.